THE DYNAMICS OF ETHNIC ARAB THOUGHT ON WOMEN'S EDUCATION IN MALANG INDONESIA - Amrullah, Zen; Supandi, Supandi; Sani, Iftitah Astria (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
Ideally, education should be accessible to everyone, both men and women, without discrimination against any group. However, in reality, educational inequality persists, especially among ethnic Arab women. This article aims to delve deeper into the perspective of the ethnic Arab community regarding women's education and to explore young women's responses to this view. This study uses a qualitative approach and case study method, with in-depth observation and interviews used for data collection. These findings reveal that educational restrictions and restrictions for ethnic Arab women are rooted in the interpretation of normative texts and binding cultural norms. Responses from ethnic Arab women to these restrictions ranged from acceptance to subtle resistance, and even active opposition. The implication of this research is that understanding how Arab ethnic thinking affects women's educational patterns in Malang can help in designing educational programs that are more inclusive and in accordance with cultural values. Provide insight into how traditional and modern values interact in the Arab community in Malang, as well as their impact on educational opportunities for women. It can be the basis for educational institutions to develop a curriculum that takes into account cultural aspects, so that women's education can be more widely accepted among ethnic Arab communities. Encourage more progressive and gender-equality-based education policies while respecting the cultural values embraced by the Arab community.